Comprehensive Strategic Management : a Guide for Students, Insight for Managers. - Bolland, Eric J. (Emerald Publishing Limited, 2017)
This breakthrough book provides students and managers alike with an understanding of the concepts and tools of strategy.
Constructing a sentiment analysis model for LibQUAL+ commentsBook review.
Keywords: Strategic planning.; Planification stratégique.; BUSINESS & ECONOMICS -- Management.; BUSINESS & ECONOMICS -- Reference.; BUSINESS & ECONOMICS -- Skills.; Strategic planning